2020
DOI: 10.1107/s2052252520007393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of crystal quality of thin protein crystals based on the dynamical theory of X-ray diffraction

Abstract: Knowledge of X-ray diffraction in macromolecular crystals is important for not only structural analysis of proteins but also diffraction physics. Dynamical diffraction provides evidence of perfect crystals. Until now, clear dynamical diffraction in protein crystals has only been observed in glucose isomerase crystals. We wondered whether there were other protein crystals with high quality that exhibit dynamical diffraction. Here we report the observation of dynamical diffraction in thin ferritin crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…1. In order to measure the X-ray topography, the crystals on the cover glass were sealed in acrylic cells, as has been reported previously Abe et al, 2020).…”
Section: Crystal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…1. In order to measure the X-ray topography, the crystals on the cover glass were sealed in acrylic cells, as has been reported previously Abe et al, 2020).…”
Section: Crystal Growthmentioning
confidence: 99%
“…This indicates that protein crystals have poor crystallinity. On the other hand, dynamic diffraction for perfect crystals of biomacromolecules such as glucose isomerase and ferritin has recently been clearly observed and analysed by rocking-curve ISSN 1600-5767 # 2021 International Union of Crystallography measurements with X-ray topography (Suzuki et al, 2017;Abe et al, 2020). However, the origin of the perfection and imperfection has not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that glucose isomerase (GI) and ferritin crystals, which are protein crystals with large d spacing, ISSN 1600-5767 can be obtained at quite high quality (Suzuki et al, 2017;Abe et al, 2020). Perfection has been characterized by the observation and calculation of oscillatory profiles of rocking curves and fringe contrasts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, clear equal-thickness fringes have also been observed for crystals of other proteins such as tetragonal HEW lysozyme (Koizumi et al, 2019) and ferritin (Abe et al, 2020). Therefore, control of the local strain in subgrains could be useful to enhance the resistance of various protein crystals to radiation damage.…”
Section: Resultsmentioning
confidence: 99%